EFEKTIVITAS TEKNIK MODELING DALAM MENINGKATKAN RASA PERCAYA DIRI SANTRI DI PONDOK PESANTREN ASSALAFI AL-FITHRAH SURABAYA - Muhammad Wildan Romdhoni; Nurul Faizah (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2018)
This research is motivated by the inequality of character development of students, particularly confidence when speaking in public. This study aims to answer the problem formulation which is reflected in the research hypothesis that modelling techniques effective in increasing the confidence of students in Pondok Pesantren Assalafi Al-Fithrah Surabaya (Ha). The approach used is a quantitative approach with the research methods true experimental design, pretest-posttest control group design. Samples were taken by purposive from the population are students of class Isti'dad Ulya A and B. The results of data analysis showed that the modeling techniques effective in improving students confidence when speaking in public in Pondok Pesantren Assalafi Al-Fithrah Surabaya.Keywords: Modeling Techniques, Self Confidence